Assessment of a Systematic Screening of Occupational Exposures in Malignant Hemopathies in the Rhone-Alpes Area: Prolymphome Study - Pérol, Olivia; Remion, Rejane; Charbotel, Barbara; Fervers, Béatrice (La Medicina del Lavoro, 2025)
Background: Several studies have highlighted the role of environmental exposures in malignant hemopathies etiology. Some patients with malignant hemopathies can be compensated as occupational diseases. The Prolymphome research aimed to assess a systematic screening of occupational exposures in patients with lymphoma or myeloma treated in three hospitals in the Rhône-Alpes region. Methods: Patients received a self-administered questionnaire to fill in at home to collect their job history and potential occupational exposures to carcinogens. A physician assessed the questionnaire to determine if a dedicated consultation was required and the possibility of claiming compensation. Patients were systematically assisted by a social worker for administrative procedures. Results: In 12 months, 754 patients were enrolled in the study, and 361 (48%) returned the questionnaire. A specialized consultation was proposed for 123 patients, and 98 patients attended the consultation. Overall, a compensation claim was proposed to 18 patients: 11 have been occupationally exposed to pesticides and seven to trichloroethylene. Conclusions: Our results confirmed the feasibility of the systematic screening procedure. Barriers were observed at every step of the process, and it underlined that patients are rarely  nformed about occupational exposures. As the prevalence of occupational exposures in malignant hemopathies remains scarce, a systematic targeted screening could be relevant in this population.